The devil and the sacred in English drama, 1350-1642 - Cox, John D., 1945- (Cambridge, U.K. ; New York : Cambridge University Press, 2000)
John Cox tells the intriguing story of stage devils from their earliest appearance in English plays to the closing of the theatres by parliamentary order in 1642. The book spans both medieval and Renaissance drama from the Mystery cycles through to plays by Greene, Marlowe, Shakespeare, Jonson, Middleton and Davenant.
Preliminaries; Contents; Illustrations; Acknowledgments; Introduction; CHAPTER ONE Stage devils and oppositional thinking; CHAPTER TWO The devil and the sacred in the English mystery plays; CHAPTER THREE Stage devils and sacramental community in non-cycle plays; CHAPTER FOUR Stage devils and early social satire; CHAPTER FIVE Protestant devils and the new community; CHAPTER SIX The devils of "Dr. Faustus"; CHAPTER SEVEN Reacting to Marlowe; CHAPTER EIGHT The devil and the sacred on the Shakespearean stage: theatre and belief; CHAPTER NINE Traditional morality and magical thinking.
Includes index.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: English drama -- Early modern and Elizabethan, 1500-1600 -- History and criticism; Devil in literature; English drama -- 17th century -- History and criticism; English drama -- To 1500 -- History and criticism; Christian drama, English -- History and criticism; Christianity and literature -- England -- History; Good and evil in literature; Holy, The, in literature; Théâtre anglais -- 16e siècle -- Histoire et critique; Démon dans la littérature.; Théâtre anglais -- 17e siècle -- Histoire et critique; Théâtre anglais -- Jusqu'à 1500 -- Histoire et critique; Christianisme et littérature -- Angleterre -- Histoire; Sacré dans la littérature.; DRAMA -- English, Irish, Scottish, Welsh; Christian drama, English; Christianity and literature; Devil in literature; English drama; English drama -- Early modern and Elizabethan; Good and evil in literature; Holy, The, in literature; England; Das Heilige; Teufel; Drama; Toneelstukken; Engels; Duivel; Het heilige; Englisch; 18.05 English literature; English drama -- To 1500 -- History and criticism; English drama -- Early modern and Elizabethan, 1500-1600 -- History and criticism; English drama -- 17th century -- History and criticism; Christian drama, English -- History and criticism; Devil in literature; Good and evil in literature; Holy, The, in literature; Evil in literature; Christianity and literature -- Great Britain -- History; To 1699; Electronic books; Criticism, interpretation, etc; History